The Primary Cilium as a Therapeutic Target in Ocular Diseases - Zhou, Peng; Zhou, Jun (Frontiers in Pharmacology, 2020)
Primary cilia are microtubule-based cellular structures located on the surfaces of most mammalian cells and play important roles in detecting external stimuli, signal transduction, and cell cycle regulation. Primary cilia are also present in several structures of the eye, and their abnormal development or dysfunction can cause various ocular diseases. The rapid development of proteomics and metabolomics technologies have helped in the identification of many ocular disease-related proteins, some of which are dysregulated in primary cilia. This review focuses on ciliary dysregulation in a number of ocular diseases and discusses the potential of targeting primary cilia in gene and stem cell therapy for these diseases.